Indicators of modernity in the orientation of Filipino women - Manalang, Priscila S.; Philippines. National Commission on the Role of Filipino Women
This paper has been derived from a study commissioned by the National Commission on the Role of Filipino Women, the primary objective of which was to ascertain the values of Filipino women by getting at their cognitions, beliefs, preferences, aspirations,, attitudinal and behavioral prepositions pertaining to the basic dimensions of human life: social, political, economic, aesthetic and philosophic.
Keywords: Women -- Philippines